2021
DOI: 10.3390/md19110611
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Pharmacological Activities of Polybrominated Diphenyl Ethers (PBDEs) from the Indonesian Marine Sponge Lamellodysidea herbacea

Abstract: Two known Polybrominated Diphenyl Ethers (PBDEs), 3,4,5-tribromo-2-(2′,4′-dibromophenoxy)phenol (1d) and 3,4,5,6-tetrabromo-2-(2′,4′-dibromophenoxy)phenol (2b), were isolated from the Indonesian marine sponge Lamellodysidea herbacea. The structure was confirmed using 13C chemical shift average deviation and was compared to the predicted structures and recorded chemical shifts in previous studies. We found a wide range of bioactivities from the organic crude extract, such as (1) a strong deterrence against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Compound 10: Off-white oil (7.0 mg, 55%); UV (MeOH) λ max (log ε) 283 (2.37) nm; 1 H NMR (DMSO-d 6 , 800 MHz) δ H 7.90 (1H, d, J = 2.3 Hz, H-3 ′ ), 7.65 (1H, d, J = 2.2 Hz, H-4), 7.57 (1H, d, J = 2.2 Hz, H-6), 7.41 (1H, dd, J = 8.8, 2.3 Hz, H-5 ′ ), 7.34 (1H, br d, J = 7.6 Hz, H-5 ′′ ), 7.32 (1H, dd, J = 7.6, 7.6 Hz, H-6 ′′ ), 7.09 (1H, br d, J = 7.6 Hz, H-7 ′′ ), 6.99 (1H, br s, H-3 ′′ ), 6.56 (1H, d, J = 8.8 Hz, H-6 ′ ), 5.14 (2H, s, H-1 ′′ ); 13 Hz, H-5 ′ ), 7.22 (1H, m, H-4 ′′ ), 7.20 (1H, m, H-5 ′′ ), 6.84 (1H, ddd, J = 8.7, 5.5, 3.1 Hz, H-7 ′′ ), 6.53 (1H, d, J = 8.8 Hz, H-6 ′ ), 5.17 (2H, s, H-1 ′′ ); 13…”
Section: Cancer Cell Cytotoxicity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 10: Off-white oil (7.0 mg, 55%); UV (MeOH) λ max (log ε) 283 (2.37) nm; 1 H NMR (DMSO-d 6 , 800 MHz) δ H 7.90 (1H, d, J = 2.3 Hz, H-3 ′ ), 7.65 (1H, d, J = 2.2 Hz, H-4), 7.57 (1H, d, J = 2.2 Hz, H-6), 7.41 (1H, dd, J = 8.8, 2.3 Hz, H-5 ′ ), 7.34 (1H, br d, J = 7.6 Hz, H-5 ′′ ), 7.32 (1H, dd, J = 7.6, 7.6 Hz, H-6 ′′ ), 7.09 (1H, br d, J = 7.6 Hz, H-7 ′′ ), 6.99 (1H, br s, H-3 ′′ ), 6.56 (1H, d, J = 8.8 Hz, H-6 ′ ), 5.14 (2H, s, H-1 ′′ ); 13 Hz, H-5 ′ ), 7.22 (1H, m, H-4 ′′ ), 7.20 (1H, m, H-5 ′′ ), 6.84 (1H, ddd, J = 8.7, 5.5, 3.1 Hz, H-7 ′′ ), 6.53 (1H, d, J = 8.8 Hz, H-6 ′ ), 5.17 (2H, s, H-1 ′′ ); 13…”
Section: Cancer Cell Cytotoxicity Assaysmentioning
confidence: 99%
“…Dysideidae sponges, such as those in the genus Lamellodysidea, are known to contain a wide variety of compounds, which generally are categorized into two distinct chemotypes: those containing highly functionalized peptides and terpenoids, and those solely containing oxygenated polyhalogenated diphenyl ethers (O-PHDEs) [1,2]. It has long been understood that while the latter chemotypes are structurally similar to anthropogenic fire retardants, there is extensive evidence for their presence in sponges to be due to their antimicrobial and antifeedant activity [3][4][5][6][7]. It is now accepted knowledge that O-PHDEs are produced by symbiotic cyanobacteria within marine sponges, with the first evidence of this claim being published in 1994, where it was found that O-PHDEs from Lamellodysidea herbacea were produced by the cyanobacterial symbiont Hormoscilla spongeliae and excreted into the aqueous sponge mesophyll [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the diverse pharmacological activities, such as antimicrobial, cytotoxicity and enzyme inhibitory properties, several PBDEs have been shown to possess ecological functions [ 67 ]. Recent research by Faisal and co-workers demonstrated that 28 and 29 confer chemical defense on the sponge host against fish herbivory by the pufferfish Canthigaster solandri and on panels of environmentally relevant pathogenic and non-pathogenic bacterial strains [ 68 ]. Such ecological functions of PBDEs could explain the widespread occurrence of the sponge in Indonesia and the Indo-Pacific region.…”
Section: Chemical Ecology-driven Discovery Of Marine Medicinesmentioning
confidence: 99%